Kualitas Bahan Bitumen Akibat Penambahan Kadar Lignin Yang Berbeda - Rukmananda, Raditya; Putra, Sasana; Karami, Muhammad (Universitas Lampung, 2018)
Asphalt is one of the materials used as a road-making material. Needs for ashpalt modification are caused by restrictions and capabilities of basic asphalt binder material to withstand pressure. Lignin functions as a binding for wood cells. Lignin is used as an additive to improve the quality of bitumen material. The binder used is 60/70 asphalt penetration. The lignin material used comes from palm oil fiber waste. The variation of lignin addition on asphalt levels is 0%, 3%, 6%, 9%. Characteristics test of asphalt carried out is Asphalt Specific Gravity, Penetration, Ductility, Softening Point, Oil Weight Loss, Viscosity. Asphalt in this study experienced an increase in quality. The best mixing of lignin is 3% and 6%. Shown by the Penetration test, the value of asphalt penetration increased to 53.6 mm. The sensitivity of asphalt to rising temperatures is indicated by the softening point test reaching 62˚C. 6% lignin mixing is the highest value for the effect of asphalt viscosity of 827 cst. The value of asphalt density reaches 1.0714 gr / cm3. In the 9% lignin mixture there is a decrease in the Ductility test, Viscosity test, Asphalt Specific Gravity test. Keywords: Asphalt, Lignin, Modification, Penetration, Viscosity.